Comparative analysis of single-stage reciprocating compressor compressing different gases - A. A. Kotlov; A. B. Burakov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Ensuring the efficient and reliable operation of reciprocating compressors is an important issue. The quality of the designed equipment is determined by the level of knowledge of the object and the perfection of methods for calculating its state. The article presents the experience of JSC «Compressor» Saint Petersburg in the creation of advanced compressor equipment. Problems of mathematical modeling, calculation, research of a reciprocating compressor with consideration of real gas properties and actual operating conditions are considered using the example of a single-stage piston compressor. A brief description of the mathematical model and engineering program for calculating and selecting rational valve parameters is given. The results of comparing the results of mathematical modeling with the results of experimental studies are obtained